Analisis Daya Saing Industri Penggilingan Padi dan Beras Indonesia di Pasar Internasional (Indo-Fintech Intellectuals: Journal of Economics and Business, 2023)
The industrial sector can be the key to a country's economic development. One of the industrial sectors that has an important role for Indonesia is the rice and rice milling industry. This study aims to analyze the development of the competitiveness of the Indonesian rice and rice milling industry in the world market and the factors that influence it. The data used in this research is secondary data with ISIC code (1063) which is time series data. Data were obtained from various sources, namely the Central Statistics Agency (BPS), UNCOMTRADE, and various other government agencies. By using multiple linear analysis techniques with the ordinary least squares (OLS) method. The results of the study show that the rice and rice milling industry has high competitiveness in the world market. Labor productivity and Revealed Comparative Advantage variables show positive and significant results for the added value of the rice and rice milling industry